Suppression of Connexin 43 Leads to Strial Vascular Hyper-Permeability, Decrease in Endocochlear Potential, and Mild Hearing Loss - Zhang, Jinhui; Wang, Xiaohan; Hou, Zhiqiang; Neng, Lingling; Cai, Jing; Zhang, Yunpei; Shi, Xiaorui (Frontiers in Physiology, 2020)
Abstract Objective: Connexin 43 (Cx43) is a protein constituent of gap junctions in some barrier cells, especially in astrocytes and microglia of the blood-brain-barrier (BBB), where it plays an important role in intercellular communication and blood barrier regulation. Despite the importance of Cx43 in other blood barriers, not much attention has been paid to expression and function of Cx43 in the blood-labyrinth-barrier (BLB) of the stria vascularis in the cochlea. Methods: We used multiple research approaches including immunocytochemical staining, a patch-clamp dye loading technique, real-time quantitative RT-PCR, Western blot, measurement of endocochlear potential (EP) with an electrode through the scala media, and auditory brainstem response to test hearing function. Results: We found Cx43 expressed in vascular endothelial cells (ECs) and perivascular resident macrophages (PVMs) in the stria vascularis of adult C57BL/6 mouse cochleae. In particular, we found the Cx43 expression in foot processes of PVMs at points of contact with endthelium. Consistent with Cx43 expression in vivo, we also found Cx43 expressed in EC-EC and EC-PVM interfaces in a co-cultured cell line model. Using a patch-clamp dye loading technique, we demonstrated that Alexa Fluor® 568 dye injected into PVMs diffuses to connected neighboring ECs. The dye diffusion between the PVMs and ECs can be blocked when the Cx43 channel was blocked by a selective Cx43 blocker, 18α‐glycyrrhetinic acid (18αGA). Suppression of Cx43 with small interfering RNA (siRNA) in vivo significantly elevated hearing threshold, and caused the endocochlear potential (EP) to drop and the blood barrier to become more permeable. In further study using in vitro primary EC cell line models, we identified that suppression of Cx43 disrupts intercellular tight junctions in the EC monolayer and increases endothelial monolayer permeability. Conculsion: Taken together, these findings underscore the importance of Cx43 expression in the normal ear for maintaining BLB integrity, normal EP, and hearing function.